Perkembangan Pendidikan Islam Klasik: Pemikiran Ilmuwan Muslim dalam Membentuk Sistem Pendidikan - Nur Afra Maulida Listiana; Achmad Junaedi Sitika; Maya Aprida Riani; Muhammad Miftah Fauzan; Mahira Allaida Putri A. Rizal; Mila Siti Hazizah (Peneliti.net, 2023)
Islamic education has grown and developed in line with the existence of Islamic preaching that has been carried out by the Prophet Muhammad SAW. Islamic education has different styles and characteristics in line with the changing times. renewal efforts in the next journey of Islamic education continues to experience changes both in terms of curriculum (subjects). This study uses a qualitative methodology with library research data collection techniques. The purpose of making this journal is to find out the main curriculum ideas in the Classical Islamic Education Tradition and to explain the thoughts of Muslim scientists regarding Classical Islamic Education. The classical Islamic education curriculum is a classical education system that is different from the current Islamic education system. When viewed from the aspect of goals, teachers, students, curriculum, methods, facilities, and infrastructure, the difference is clear. There have been many developments in the world of Islamic education. The term classical Islamic education is a process of teaching and learning activities carried out by individuals, certain groups or government/institutions, formal or non-formal, within a certain period of time during the growth and development of Islam.